2021
DOI: 10.1016/j.vaccine.2021.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine effectiveness against infection and onwards transmission of COVID-19: Analysis of Belgian contact tracing data, January-June 2021

Abstract: In Belgium, high-risk contacts of an infected person were offered PCR-testing irrespective of their vaccination status. We estimated vaccine effectiveness (VE) against infection and onwards transmission, controlling for previous infections, household-exposure and temporal trends. We included 301,741 tests from 25 January to 24 June 2021. Full-schedule vaccination was associated with significant protection against infection. In addition, mRNA-vaccines reduced onward transmission: VE-estimates increased to >90% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 14 publications
2
51
1
Order By: Relevance
“…Around the world, massive vaccination campaigns started in early 2021 and data about the immunological response emerged in the literature to document the evolution of humoral response in subjects vaccinated against SARS-CoV-2 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In most seronegative subjects, antibody response was positive two weeks after the first dose and the peak response was observed around 28 days [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Around the world, massive vaccination campaigns started in early 2021 and data about the immunological response emerged in the literature to document the evolution of humoral response in subjects vaccinated against SARS-CoV-2 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In most seronegative subjects, antibody response was positive two weeks after the first dose and the peak response was observed around 28 days [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Around the world, massive vaccination campaigns started in early 2021 and data about the immunological response emerged in the literature to document the evolution of humoral response in subjects vaccinated against SARS-CoV-2. [8][9][10][11][12][13][14][15] In the majority of seronegative subjects, antibody response was positive two weeks after the rst dose and the peak response was observed around 28 days. 13,16 The antibody titers were also higher in previously infected individuals compared to seronegative subjects and recent studies found a decline in antibody titers at 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Belgium, based on a similar contact tracing system, also described significant protection against infection after a close contact; however, the study only examined fully vaccinated IPs. Moreover, additional protection against transmission was demonstrated when the CP was also fully vaccinated [20]. A retrospective analysis from England confirmed lower transmission to close contacts among vaccinated persons for the Alpha variant and the same effect but somewhat less pronounced for the Delta variant [21].…”
Section: Discussionmentioning
confidence: 89%